Fire Disaster Trauma Healing for Children in Kampung Pulau Bromo through Play Therapy - Dina Rafidiyah (UMBanjarmasin, 2021)
These community service chains are some activities done for children in Kampung Pulau Bromo. Around a year earlier, a fire disaster happened that made fifty-five people lose their houses. The disaster has caused traumas for the community. While adults can express their traumatic experience of losing their houses, children find it difficult to express their traumas. Therefore, the community service team from Universitas Muhammadiyah Banjarmasin tried to make several fun programs or activities to cope with these problems. Five planned fun activities were conducted and one bonus activity for the children in Kampung Pulau Bromo through play therapy with singing, playing, demonstrating, etcetera. The results were awe-inspiring. The children always feel happy after every activity. Even though it needs years to heal the trauma caused by a disaster such as fire, hopefully, these community services can bring positive impacts to the children who had tin Kampung Pulau Bromo.